2009
DOI: 10.1345/aph.1l426
|View full text |Cite
|
Sign up to set email alerts
|

Intricacies of Bevacizumab-Induced Toxicities and Their Management

Abstract: As bevacizumab is becoming widely used in general oncology practice, it is important to understand the toxicities that can arise and to develop practice guidelines for their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 57 publications
7
126
0
4
Order By: Relevance
“…On the basis of cumulative adverse events observed in the expanded cohort of 1.6 mg/kg, the recommended phase II dose level of dalantercept as monotherapy is 1.2 mg/kg (75% of 1.6 mg/kg) every 3 weeks. In the present study, no clinically relevant hypertension, proteinuria, gastrointestinal perforations, or hemorrhage were observed, and thus the safety profile of dalantercept appears to be distinct from that of VEGF pathway inhibitors (32)(33)(34)(35). This result suggests that dalantercept potentially could be administered concurrently with a VEGF pathway inhibitor to achieve enhanced antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 45%
“…On the basis of cumulative adverse events observed in the expanded cohort of 1.6 mg/kg, the recommended phase II dose level of dalantercept as monotherapy is 1.2 mg/kg (75% of 1.6 mg/kg) every 3 weeks. In the present study, no clinically relevant hypertension, proteinuria, gastrointestinal perforations, or hemorrhage were observed, and thus the safety profile of dalantercept appears to be distinct from that of VEGF pathway inhibitors (32)(33)(34)(35). This result suggests that dalantercept potentially could be administered concurrently with a VEGF pathway inhibitor to achieve enhanced antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 45%
“…One of the best studied agents is the monoclonal anti-VEGF antibody, bevacizumab. Toxicities associated with bevacizumab include neutropenia, with previously published reports indicating increased incidence of neutropenia in subjects assigned to the bevacizumab containing arms of phase 2 and 3 clinical trials [33,34] . Recently, two large prospective, randomized, phase 3 clinical trials evaluating use of bevacizumab in ovarian cancer were published.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhage is one of the most severe toxicities associated with VEGFIs [46]. Bevacizumab has the highest frequency of bleeding, and although a pooled analysis of three randomized trials did not demonstrate a significantly higher incidence of grade 3-4 hemorrhage [47], numerous trials have individually reported higher incidences of bleeding [47].…”
Section: Hemorrhagementioning
confidence: 99%
“…Grade 3-4 hemorrhagic events with bevacizumab occur at a rate of 1.2%-4.6%. However, less severe bleeding occurs in up to 40% of patients [46,48]. The SMTKIs have so far been associated with a lower rate of bleeding, but events including fatal pulmonary and intracranial hemor- [49,50].…”
Section: Hemorrhagementioning
confidence: 99%